Perioperative routines and surgical techniques for saphenous vein harvesting in CABG surgery: a national cross-sectional study in Sweden - Larsson, Hanna (J Cardiothorac Surg, 2020)
BACKGROUND: The saphenous vein is the most commonly used conduit for coronary artery bypass grafting (CABG). Wound healing complications related to saphenous vein harvesting are common, with reported surgical site infection rates ranging from 2 to 20%. Patients’ risk factors, perioperative hygiene routines, and surgical technique play important roles in wound complications. Here we describe the perioperative routines and surgical methods of Swedish operating theatre (OT) nurses and cardiac surgeons. METHODS: A national cross-sectional survey with descriptive design was conducted to evaluate perioperative hygiene routines and surgical methods associated with saphenous vein harvesting in CABG. A web-based questionnaire was sent to OT nurses and cardiac surgeons at all eight hospitals performing CABG surgery in Sweden. RESULTS: Responses were received from all hospitals. The total response rate was 62/119 (52%) among OT nurses and 56/111 (50%) among surgeons. Chlorhexidine 5 mg/mL in 70% ethanol was used at all eight hospitals. The OT nurses almost always (96.8%) performed the preoperative skin disinfection, usually for three to 5 minutes. Chlorhexidine was also commonly used before dressing the wound. Conventional technique was used by 78.6% of the surgeons, “no-touch” by 30.4%, and both techniques by 9%. None of the surgeons used endoscopic vein harvesting. Type of suture and technique used for closing the wound differed markedly between the centres. CONCLUSIONS: In this article we present insights into the hygiene routines and surgical methods currently used by OT nurses and cardiac surgeons in Sweden. The results indicate both similarities and differences between the centres. Local traditions might be the most important factors in determining which procedures are employed in the OT. There is a lack of evidence-based hygiene routines and surgical methods.